Symptomatic hypotensive episodes in patients with hypertension. Relationship with blood pressure self-monitoring parameters - S. A. Ermasova; I. M. Sokolov; Yu. G. Shvarts (Российский кардиологический журнал)
Aim. To study the relationship between symptomatic hypotensive episodes (SHEs) and parameters of self-monitoring of blood pressure (SMPB) in patients with hypertension (HTN).Material and methods. A total of 77 patients from 40 to 76 years old with HTN were examined. To identify SHEs, an original questionnaire was used. Patients underwent SMBP in the morning and evening, as well as recorded SHE in the diary. The self-monitoring period lasted 4 weeks. Patients without prior myocardial infarction and/or stroke are conventionally called “uncomplicated” HTN, while with cardiovascular events in history — “complicated” HTN.Results. According to the questionnaire, 48 (62,3%) patients noted SHEs. Uncomplicated HTN was recorded in 19 (51,4%) participants, while complicated one — in 29 (72,5%) (p=0,05). Blood pressure during SHEs was on average higher in patients with complicated HTN than in uncomplicated HTN (103/60 vs 95/60 mm Hg (p=0,05)). With a combination of uncomplicated HTN and SEG, mean systolic blood pressure (SBP) (125,9±10,5 vs 137,9±8,2 mm Hg), evening SBP (125,3±8,1vs 133,3±10,4 mm Hg), maximum SBP (149,8±11,8 vs 161,7±12,1 mm Hg) in the morning, as well as minimum SBP in the evening (101,8±10,8 vs 113,7±9,7 mm Hg) were lower than in patients without SHEs (p<0,05).In complicated HTN, an opposite relationship was observed: patients with SHEs had higher mean SBP (133,49±12,4 vs 118,93±15,3 mm Hg), maximum SBP (162,8±11,6 vs 141,7±12,0 mm Hg), and diastolic blood pressure (DBP) (91,5±5,6 vs 83,5±8,8 mm Hg) in the morning (p<0,05), as well as higher variability of morning (11,8±2,1 vs 8,2±2,7 mm Hg) and evening SBP (11,9±4,2 vs 8,6±3,2 mm Hg) compared with patients without SHEs (p<0,05). There were no significant differences in antihypertensive therapy.Conclusion. More than half of patients with hypertension report SHEs. SHEs in patients without prior myocardial infarction and/or stroke were characterized by lower blood pressure level than in subjects with prior cardiovascular events. Among patients with SHEs without cardiovascular events, the values of morning, evening, and maximum SBP in the morning are lower than in patients without SHEs. In patients with complicated HTN and SHEs, the opposite trend was observed: higher SBP and DBP in the morning, as well as greater variability of morning and evening SBP, in comparison with those without SHEs. These patterns cannot be explained by the antihypertensive drugs taken.